Characterisation of a new cell wall teichoic acid produced by Listeria innocua ŽM39 and analysis of its biosynthesis genes. (January 2022) - Bellich, Barbara; Janež, Nika; Sterniša, Meta; Klančnik, Anja; Ravenscroft, Neil; Rizzo, Roberto; Sabotič, Jerica; Cescutti, Paola
Abstract: Listeria innocua is genetically closely related to the foodborne human pathogen Listeria monocytogenes . However, as most L. innocua strains are non-pathogenic, it has been proposed as a surrogate organism for determining the efficacy of antimicrobial strategies against L. monocytogenes . Teichoic acids are one of the three major cell wall components of Listeria, along with the peptidoglycan backbone and cell wall-associated proteins. The polymeric teichoic acids make up the majority of cell wall carbohydrates; the type of teichoic acids directly attached to the peptidoglycan are termed wall teichoic acids (WTAs). WTAs play vital physiological roles, are important virulence factors, antigenic determinants, and phage-binding ligands. The structures of the various WTAs of L. monocytogenes are well known, whereas those of L. innocua are not. In the present study, the WTA structure of L. innocua ŽM39 was determined mainly by 1D and 2D NMR spectroscopy and it was found to be the following: [→4)-[α-D-Glc p NAc-(1→3)]-β-D-Glc p NAc-(1→4)-D-Rbo-(1P→]n This structure is new with respect to all currently known Listeria WTAs and it shares structural similarities with type II WTA serovar 6a. In addition, the genome of strain L. innocua ŽM39 was sequenced and the majority of putative WTA synthesis genes were identified. Graphical abstract: Image 1 Highlights: WTA was isolated from the foodborne Listeria innocua ŽM39 strain. The structure of the L. innocua ŽM39 WTA was determined by NMR to be new. In L. innocua WTA the disaccharide α-GlcNAc-(1→3)-β-GlcNAc is linked to C4 of Rbo Putative WTA synthesis genes were identified in the genome.